(3COYjI ddEeGe Ydi cQe Gddg hLggs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3MOKfG GdSjO GdCLd fLe GdOjf Hf jMji GdYdhi GdMSjfi bGd dbjJ jMji Hf RjO Hf Ydi Ydjg GdSdGe hgh eJhLg Edi NQGSGf aSdeJ Ydjg s
(3BNQgG (B:s
(3hcGf ai OYGFg Ydjg GdSdGe EPG GYJQa HGdJbUjQ Yf JCOjIj GdTcQ cGf TcQ YHGOc GdPi ChLH Ydjg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs